Structural chemistry and spin-glass behaviour of Nd 18Li 8Fe 4TiO 39 - Thammajak, N; Battle, P; Grandjean, F; Long, G; Ramos, S (2012)
Nd 18Li 8Fe 4TiO 39 has been synthesised and characterised by neutron powder diffraction, X-ray absorption spectroscopy, Mössbauer spectroscopy and magnetometry. The cubic structure (Pm3n, a=11.97227(8) Å) is based on intersecting 〈1 1 1〉 chains comprised of alternating octahedral and trigonal-prismatic coordination sites. These chains lie within hexagonal-prismatic cavities formed by a NdO framework. The larger of the two crystallographically distinct octahedral sites, 8e, is occupied by iron, titanium and lithium in a ratio of 76:20:4; the smaller, 2a, is occupied by iron and titanium in a ratio of 79:21. The trigonal-prismatic site, 16i, is occupied by lithium and iron in a ratio of 98:2. The cations on the 2a sites are assigned as Ti 4and low-spin Fe 4, and those on the 16i sites as Li and Fe 3. The 8e sites are thought to be occupied by Li, Fe 3 and Ti 3. Nd 18Li 8Fe 4TiO 39 undergoes a transition to a spin-glass state at 4.25(5) K. © 2012 Elsevier Inc. © 2012 Elsevier Inc. All rights reserved.